Understanding the relation between creep-fatigue fracture mechanisms and intergranular dislocation accommodation of a high chromium steel using nanoindentation characterization. (June 2022) - Song, Yuxuan; Yu, Ting; Chen, Hongyu; Jin, Weiya; Gao, Zengliang; Terfa Debela, Tekalign; Wu, Zhenggang; Ma, Yi
Highlights: The creep-fatigue fracture mechanism of P92 steel was studied by nanoindentation. Longer cyclic life of P92 steel under CF loading with shorter dwells. The fracture mechanism shifts from fatigue to CF damage with increasing dwell time. A normalized damage indicator is proposed to characterize the fracture mechanism. Abstract: Relying on nanoindentation technology, the effect of intergranular dislocation accommodation on fracture behavior for the P92 steel that had experienced creep-fatigue (CF) loading was studied. The results indicate that the fracture mechanism of P92 steel gradually changes from fatigue-dominating to creep-fatigue interactive damage with increasing dwell time. According to the variations of hardness ( H ), elastic modulus ( E ), creep resistance and strain rate sensitivity ( m ), a normalized damage indicator ln( H / E )/ m is proposed to characterize the fracture mechanism. Thermally activated process of intergranular dislocation accommodation results in the formation of creep voids at GBs and a remarkable stress relaxation, leading to a creep-fatigue fracture mechanism for the CF specimens with long dwells. However, mechanically driven of dislocation accommodation contributes to enhanced grain size and lower hardness, resulting in a fatigue-dominated fracture mechanism.